THE STRATEGIC MANAGEMENT TOOLS FOR HIGHER EDUCATION INSTITUTIONS - V. Voloshina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2014)
The strategic management tools have been investigated in the article. Their definition and classification has been improved. The strategic management tools for use in higher education institutions have been singled out in the study according to the stages of strategic management.